GNAS Epigenetic Defects and Pseudohypoparathyroidism: Time for a New Classification? - Mantovani, G.; Elli, F. M.; Spada, A. (Hormone and Metabolic Research, 2012)
Pseudohypoparathyroidism-Ia and -Ib (PHP-Ia and -Ib) are caused by mutations in GNAS exons 1–13 and methylation defects in the imprinted GNAS cluster, respectively. PHP-Ia patients show Albright hereditary osteodystrophy (AHO), together with resistance to the action of different hormones that activate the Gs-coupled pathway. In PHP-Ib patients AHO is classically absent and hormone resistance is limited to PTH and TSH. This disorder is caused by GNAS methylation alterations with loss of imprinting at the exon A/B differentially methylated region (DMR) being the most consistent and recurrent defect. The familial form of the disease (AD-PHP-Ib) is typically associated with an isolated loss of imprinting at the exon A/B DMR due to microdeletions disrupting the upstream STX16 gene. In addition, deletions removing the entire NESP55 DMR, located within GNAS, associated with loss of all the maternal GNAS imprints have been identified in some AD-PHP-Ib kindreds. Conversely, most sporadic PHP-Ib cases have GNAS imprinting abnormalities that involve multiple DMRs, but the genetic lesion underlying these defects is unknown. Recently, methylation defects have been detected in a subset of patients with PHP-Ia and variable degrees of AHO, indicating a molecular overlap between the 2 forms. Imprinting defects do not seem to be associated with the severity of AHO neither with specific AHO signs. In conclusion, the latest findings on the molecular basis underlying these defects suggest the existence of a clinical and genetic/epigenetic overlap between PHP-Ia and PHP-Ib, and highlight the necessity of a new clinical classification of these disorders based on molecular findings.
Keywords: pseudohypoparathyroidism; Albright hereditary osteodystrophy; GNAS; imprinting